Pengaturan Pelaksanaan Dinas Jaga di Kapal Sesuai STCW 1978 as Amended 2010 - Kholid Mawardi (Sekolah Tinggi Maritim Yogyakarta, 2021)
The duty officer has an important role in managing the ship's motion while sailing to avoid things that are not desirable to avoid collision hazards. The purpose of this study was to regulate the implementation of the guard service in preventing collision hazards in MT. FORTUNE GLORY XLI, optimizing the use of navigation tools to prevent collision hazards and the efforts made in emergency conditions. The research method uses qualitative. The result of the research is that the implementation of the guard service on the ship has not been carried out correctly because the duty officer did not carry out his guard duty, did not have confidence as a new graduate officer when carrying out guard duty on the bridge and the use of navigation tools was not optimal. Division of guard duties on board the MT. FORTUNE GLORY XLI has complied with the stipulated regulations but in its implementation there are irregularities because the First Officer as a senior official is not responsible when carrying out his guard duties, the lack of confidence as a new graduate and the use of navigation tools that are less than optimal by the officers causes results what is obtained is not optimal.